Proton linear accelerator for boron-neutron capture therapy - Sanin, V.M.; Bomko, V.A.; Zaitsev, B.V.; Zadvorny, A.S.; Kobets, A.P.; Mazalov, Yu.P.; Ptukhina, Z.E.; Rudjak, B.I. (Вопросы атомной науки и техники, 1999)
At the present time radiotherapy, surgery and chemotherapy are the main methods of treatment of malignant tumors. They may be used individually or in combination with other methods.